Dipta Garments Limited. (DIRD Group) HRM & Compliance, Production, IE, Merchandising and Commercial - Hossain, Md. Shorif (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Post Graduate Diploma in Knitwear Industry Management, 2021.